Lung-protective effect of Punicalagin on LPS-induced acute lung injury in mice. Issue 1 (28th January 2022) - Zeng, Yibin; Zhao, Hongying; Zhang, Tong; Zhang, Chao; He, Yanni; Du, Lingbo; Zuo, Fuguo; Wang, Wuqing
Abstract: Background: Punicalagin (Pun) is one of the main bioactive compounds in pomegranate peel, it possesses many properties, including antioxidant, anti-inflammation and immunosuppressive activities. The study was aimed to investigate the protective effect and mechanisms of Pun on lipopolysaccharide (LPS)-induced acute lung injury (ALI) in mice. Methods and Results: Forty-eight BALB/c male mice were used to establish ALI by intratracheal-instilled 2.4 mg/kg LPS, the mice were randomly divided into model and Pun (10, 20, 40 mg/kg) groups. The other 12 mice were intratracheal-instilled same volume of water as control. After 2 h of receiving LPS, mice were administered drug through intraperitoneal injection. Lung index, histopathological changes, white blood cells and biomarkers in bronchoalveolar lavage fluid (BALF) were analyzed. The protein expression of total and phosphor p65, IκBα, ERK1/2, JNK and p38 in lung tissue was detected. The result showed that Pun could reduce the lung index and wet/dry weight (W/D) ratio, improve lung histopathological injury. In addition, Pun decreased the inflammation cells and regulated the biomarkers in BALF. Furthermore, Pun dose-dependently reduced the phosphor protein levels of p65, IκBα, ERK1/2, JNK and p38 in lung tissue, which exhibited that the effect of Pun related to mitogen-activated protein kinases (MAPKs) pathway. More importantly, there was no toxicity was observed in the acute toxicity study of Pun. Conclusion: Pun improves LPS-induced ALI mainly through its anti-inflammatory properties, which is associated with nuclear factor-κB (NF-κB) and MAPKs signaling pathways. The study implied that Pun maybe a potent agent against ALI in future clinic.